2016
DOI: 10.1111/1475-6773.12516
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hypertension in Primary Care Safety‐Net Clinics in the United States: A Comparison of Community Health Centers and Private Physicians' Offices

Abstract: Increasing physician use of fixed-dose combination drugs may be particularly helpful in improving hypertension control at CHCs where there are higher rates of uncontrolled hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Compared with free‐equivalent combinations, use of fixed‐dose combination (FDC) therapies in patients who require combination medicines is believed to improve adherence to antihypertensive drugs as it reduces pill burden . However, studies reported that the use of FDCs in patients taking two or more guideline‐recommended antihypertensive medications was relatively low in clinical practices, from 10% to 50% . This meta‐analysis, which includes the latest studies, aimed to systemically evaluate the impact of FDCs on hypertensive medication adherence compared with free‐equivalent combination therapies according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and Meta‐Analysis of Observational Studies in Epidemiology (MOOSE) guidelines …”
Section: Introductionmentioning
confidence: 99%
“…Compared with free‐equivalent combinations, use of fixed‐dose combination (FDC) therapies in patients who require combination medicines is believed to improve adherence to antihypertensive drugs as it reduces pill burden . However, studies reported that the use of FDCs in patients taking two or more guideline‐recommended antihypertensive medications was relatively low in clinical practices, from 10% to 50% . This meta‐analysis, which includes the latest studies, aimed to systemically evaluate the impact of FDCs on hypertensive medication adherence compared with free‐equivalent combination therapies according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) and Meta‐Analysis of Observational Studies in Epidemiology (MOOSE) guidelines …”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, some evidence suggests that CHCs may be more likely to escalate care for chronic conditions, like uncontrolled hypertension, compared with private practices. 24 During the same time period as our study, there was a concerted national effort to reform healthcare delivery and certify FQHCs as patient-centered medical homes (PCMH). PCMH adoption was, in turn, associated with improvements Fig.…”
Section: Discussionmentioning
confidence: 99%
“…hypertension control may be because HCs with a higher concentration of these patients spent more intensive effort on improving these outcomes, or more diabetes patients sought care from these organizations if they offered diabetes specific services such as lifestyle or exercise classes [40,41]. Among clinical quality measures, few control variables systematically explained urban/rural differences.…”
Section: Plos Onementioning
confidence: 99%